Utilisation Of Matured Green Banana (Musa Paradisiaca Var. Awak) Flour And Oat Beta Glucan As Fibre Ingredients In Noodles - Chong Li, Choo (2017)
The purpose of this study was to increase the dietary fibre content and enhance the nutritional values of yellow alkaline noodle (YAN). In this study, banana flour (BF) from mature green banana (Musa paradisiacal var. Awak) and oat 13- glucan were incorporated as sources of fibre in YAN. The effects of adding increasing level (20% to 50%) of BF and 10% oat 13- glucan on the physical, chemical , sensory and shelf-life properties of YAN were investigated.